Aspek Cognitive, Affective dan Siubjective Norm dalam Keputusan - Pembelian Konsumen Pada Industri Jasa Penerbangan di Yogyakarta - Santi Santi; Gidion P. Adirinekso (Fakultas Bisnis UKDW, 2006)
This research tries to analyze the fficts of cognitive aspect,affictive aspect and subjective norm on consumer purchasing behavior in the services of Air Transportation Industries in Yog'takarta. Reason Action Theory that is suggested by Ajzen and Fishbein (1980) is used to develop research model. The model is composed of attitudinal, social influence and intention variables to predict iehavior. The theory assertsthat the intention to perform behavior is determined by the individual attitude towards performing the behavior and subjective norm that are held by an individual.To solve the problem, this research uses Structural EquationModel (SEITI) technique to test research hypothesis with 186 samples that have been gathered with purposive random sampling method. In this research, attitude has been measured by cognitive aspect (reliability, empathy, ossurance and responsiveness) and affective aspect (facility, equipment and ambience), and subjective norrn by group of references (family andfriends).The result shows that cognitive and affective aspect has positiveand significant ffict to consumer behavior. The attitude also haspositive and significant ffict to consumer behavior. This result supports Kirk L. Wakefield and J